Comparison of Amblyopia Treatment Effect with Dichoptic Method Using Polarizing Film and Occlusion Therapy Using an Eye Patch - Yo Iwata; Tomoya Handa; Hitoshi Ishikawa (MDPI AG, 2022)
We developed a novel, low-cost, easily administered method that uses a polarizing film to enable dichoptic treatment for amblyopia. In this study, we compared its effects with occlusion therapy using an eye patch. Fifty-eight patients (aged 4.7 ± 1.0 years) diagnosed with anisometric amblyopia were included and instructed to wear complete refractive correction glasses with either occlusion therapy using an eye patch (eye patch group) or dichoptic treatment using polarizing film (polarizing film group) for 2 h per day. We examined the improvement in the visual acuity and compliance rate of the patients 2 months after treatment initiation. After treatment, the polarizing film group showed significant improvement in visual acuity compared with the eye patch group. Moreover, the compliance rate was significantly better in the polarizing film group than in the eye patch group. In both groups, there was a significant correlation between the improvement in visual acuity and compliance rate. This new dichoptic treatment using a polarizing film was shown to be effective for anisometropic amblyopia.